'Non multa, sed multum': EU Roma policy and the challenges of Roma inclusion. Issue 4 (7th June 2018) - Iusmen, Ingi
Abstract: The Roma face widespread discrimination and marginalisation in the EU. To address these, the Commission adopted an EU Roma policy—'EU Framework for National Roma Integration Strategies' (2011)—which is implemented with the support of EU legal, financial and soft law instruments. This paper investigates the effectiveness and implications of EU Roma policy in addressing the social exclusion and discrimination faced by the Roma by assessing the policy framing, the key EU instruments and whether they address the root causes of Roma marginalisation. It is argued that the socio-economic framing of Roma exclusion—underpinning the EU Roma policy—along with the EU instruments upholding its implementation, both blurred the responsibility boundaries for Roma inclusion between the EU and national levels, and also proved ineffective and ill-designed in addressing the root causes of Roma exclusion and discrimination.